Impacto social y ambiental de la minería aurífera en el Bajo Cauca antioqueño (2024)
The purpose of this monograph is to study the social and environmental impacts generated by gold mining in the Bajo Cauca subregion of Antioquia, located in the north of the country. The activity to be studied in depth is gold extraction, which represents 90% of the economic value of the region in recent years, which is contrasted by the social and environmental impacts, since more than 40,000 hectares have been transformed into contaminated, deforested and desert areas (Cuevas, 2014). The representation of Bajo Cauca in terms of extracted gold is almost 60% in the department of Antioquia and 40% in the country, being the most important source of profit in the region (Bonilla-Calle, 2023a).